2011
DOI: 10.1007/s12663-011-0208-y
|View full text |Cite
|
Sign up to set email alerts
|

Are People Aware of Oral and Maxillofacial Surgery in India?

Abstract: Introduction Maxillofacial surgery is one of the most rapidly expanding specialities in India. There is however a very poor understanding of the scope of the speciality. This paper attempts to find out the awareness of the speciality in India. Materials and methods A questionnaire was given to 50 medical, dental undergraduate students, 50 medical and dental practitioners, and 50 lay persons giving us a total of 250 responses. 10 common anomalies were chosen and they were asked to choose the most appropriate sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 2 publications
0
11
0
1
Order By: Relevance
“…In study done by Reddy et al [1] they found that all study groups were not clear about the scope of the specialty and its capabilities. All groups were aware that impactions, implants, trauma are treated by maxillofacial surgeons.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…In study done by Reddy et al [1] they found that all study groups were not clear about the scope of the specialty and its capabilities. All groups were aware that impactions, implants, trauma are treated by maxillofacial surgeons.…”
Section: Discussionmentioning
confidence: 96%
“…It is an internationally recognized surgical specialty. In some countries, including the United States, it is a recognized specialty of dentistry; in others, including the UK, it is recognized as a medical specialty [1].…”
Section: Introductionmentioning
confidence: 99%
“…The scope of the OMFS improved from simple surgical procedures such as dentoalveolar surgeries and basic maxillofacial trauma to more advanced procedures like management of pathologies of head and neck (both benign and malignant), bone grafting, craniofacial surgery, TMJ surgery, cleft lip and palate, facial deformities correction, aesthetic facial surgery, implant surgery, etc [ 1 ] [ 5 ]. Also, OMFS deals with non - surgical difficulties affecting the orofacial area like the treatment of facial pain or oral mucosal disease [ 1 ] [ 6 ].…”
Section: Discussionmentioning
confidence: 99%
“…It is considered a branch of dentistry in countries such as the United States; because in the United Kingdom, it is considered a medical specialty. 3 Oral and maxillofacial surgeons examine and treat dental and medical emergency cases; they also receive referrals from professionals within these specialties. OMFS is one of the few branches of dentistry that is linked to and interacts with other medical specialties.…”
Section: Introductionmentioning
confidence: 99%